Radiation-induced cystitis treated with hyperbaric oxygen therapy (RICH-ART): long-term follow-up of a randomised controlled, phase 2-3 trial - Oscarsson, Nicklas; Rosén, Anders; Müller, Bernd; Koskela, Lotta Renström; Giglio, Daniel; Kjellberg, Anders; Ettala, Otto; Seeman-Lodding, Helén (ELSEVIER, 2025)
Background
Chronic radiation-induced cystitis is a common and often debilitating complication of radiotherapy for pelvic cancers, affecting approximately 5-10% of patients. Symptoms such as haematuria, urinary urgency, frequency, and dysuria significantly affect quality of life. Although hyperbaric oxygen (HBO2) alleviates symptoms, evidence regarding its long-term benefits is limited. This study reports on the 5-year follow-up of the RICH-ART trial, evaluating whether the therapeutic effects of HBO2 on chronic radiation-induced cystitis are sustained over a longer follow-up period.
Methods
RICH-ART is a multicentre, open-label, phase 2-3 trial, conducted at five Nordic hospitals: Sahlgrenska and Karolinska (Sweden), Haukeland (Norway), Rigshospitalet (Denmark), and Turku (Finland). Eligible patients were aged 18-80 years, had completed pelvic radiotherapy at least 6 months earlier, had chronic radiation-induced cystitis, and an Expanded Prostate Cancer Index Composite (EPIC) urology score <80. Patients were randomised to receive HBO2 (30-40 sessions, 100% oxygen, breathed at 240-250 kPa, for 80-90 min daily) or standard of care with no restrictions for other medications or interventions (control group). No masking was applied. The primary outcome-change in EPIC urinary total score from baseline to 6 months- has been previously reported. After this point, patients in the control group were offered HBO2. Here, we report the secondary outcome: longterm symptom relief in all patients who received HBO2, measured as change in EPIC urinary total score from baseline to 5 years post-HBO2. Adverse events were recorded only during the period patients received HBO2. Follow-up was terminated 6 months early, in May 2022, due to administrative constraints, primarily lack of funding. RICH-ART is registered with ClinicalTrials.gov (NCT01659723), and with EudraCT (2012-001381-15).
Findings
Of 223 patients screened between May 9, 2012, and Dec 20, 2017, 87 were enrolled and randomised. One patient in the intervention group and 7 patients in the control group withdrew consent immediately after randomisation. Of the remaining 79 patients, 74 completed the first part of the study. One patient in the control group declined HBO2 and three had missing data for the first year, making 70 patients eligible for follow-up. The mean EPIC urinary total score improved 18.0 points (95% CI 14.2-21.8) from 46.6 (SD 18.4) pre-HBO2 to 64.6 (SD 24.1) at 6 months, and the improvement remained stable at 19.1 points (95% CI 13.3-24.9) at year 5. Responders (n = 48; 68.6%), defined as those with >= 9-point improvement post-HBO2, maintained a mean increase of 22.9 (95% CI 16.2-29.6; p < 0.0001) at 5 years. Non-responders (n = 22; 31.4%) showed no early benefit (43.5 [SD 15.6] to 44.6 [SD 16.6]). Nine of the 70 patients (12.8%) received additional HBO2 for recurring symptoms.
Interpretation
Our findings provide evidence for the long-term effects of HBO2 in the treatment of chronic radiation-induced cystitis. Sustained symptom relief over 5 years supports its potential as a key therapeutic option for managing chronic radiation-induced adverse effects. Further studies are needed to define optimal treatment protocols, identify predictive biomarkers, and evaluate health economic impact.